(untitled) (Czech Journal of International Relations, 1994)
After the end of the Cold War and the bipolar confrontation, the proliferation of weapons of mass destruction, especially nuclear weapons, is identified as one of the greatest risks of today. The current US administration attaches particular importance to the fight against the proliferation of nuclear weapons. This is especially evidenced by Clinton’s statement at the UN in September of last year that "no democracy will be able to feel safe until we manage to solve the problem of the most destructive weapons". The proliferation of nuclear weapons is an extremely serious and complex problem that requires assessment from many perspectives, which is understandably beyond the capabilities of one article and one author. In one article, at most, attention can be drawn to the need to analyze certain contexts - in this case, primarily historical, political and international-non-political contexts. Based on this analysis, it is then possible to outline the basis of the forecast of two key questions, which are as follows: 1. What will happen if some countries of the so-called third world arm themselves with these weapons? 2. What will happen if developing countries with dictatorial regimes acquire nuclear weapons?